TEACHING WITH TASTE: HEALTHY FOOD IN EARLY CHILDHOOD EDUCATION AS A TOOL FOR LEARNING AND INTERACTION - Benvindo de Souza, Cirlene; Silva Medrado, Idália; Ribeiro Santana, Josilene (Revista Gênero e Interdisciplinaridade, 2025)
The article Teaching with Flavor explores the importance of introducing healthy eating habits in early childhood education as a tool for learning and social interaction. Through the project Eating Well to Sing, Dance and Live Better, children from CMEI Castelo Encantado participated in fun and practical activities, such as planting sweet potatoes and sensory experiments, which incorporated cultural and scientific elements. This approach actively engaged the children, promoting cognitive, motor and social skills, in addition to raising awareness about nutrition and sustainability. With positive results, the project encouraged both children and their families to adopt more conscious and balanced food choices.